Motivators of and barriers to becoming a COVID‐19 convalescent plasma donor: A survey study. Issue 3 (27th December 2020) - Masser, Barbara M.; Ferguson, Eamonn; Thorpe, Rachel; Lawrence, Claire; Davison, Tanya E.; Hoad, Veronica; Gosbell, Iain B.
Abstract: Objectives: To determine the motivators and barriers to COVID‐19 convalescent plasma donation by those in the United Kingdom who have been diagnosed with or who have had symptoms of SARS‐CoV‐2 (COVID‐19) but who have not donated. Background: Convalescent plasma from people recovered from COVID‐19 with sufficient antibody titres is a potential option for the treatment and prevention of COVID‐19. However, to date, recruiting and retaining COVID‐19 convalescent plasma donors has been challenging. Understanding why those eligible to donate COVID‐19 convalescent plasma have not donated is critical to developing recruitment campaigns. Methods/Materials: A total of 419 UK residents who indicated that they had been infected with COVID‐19 and who lived within 50 km of sites collecting COVID‐19 convalescent plasma completed an online survey between 25th June and 5th July 2020. Respondents completed items assessing their awareness of convalescent plasma, motivations and barriers to donation and intention to donate COVID‐19 convalescent plasma. Results: Awareness of COVID‐19 convalescent plasma was low. Exploratory factor analysis identified six motivations and seven barriers to donating. A stronger sense of altruism through adversity and moral and civic duty were positively related to intention to donate, whereas generic donation fears was negatively related. Conclusions: Once potential donors are aware of convalescent plasma, interventions should focus on the gratitude and reciprocity that those eligible to donate feel, along with a focus on (potentially) helping family and norms of what people ought to do. Fears associated with donation should not be neglected, and strategies that have been successfully used tor recruit whole‐blood donors should be adapted and deployed to recruit COVID‐19 convalescent plasma donors.